Experiences from an online interview-based study conducted in a juvenile correctional institution - Izsák Hajnalka (ЗУІ ім. Ференца Ракоці ІІ, 2025)
Abstract. The integration of digital technologies into qualitative research has significantly reshaped data collection methodologies, with online interviewing emerging as a vital tool for social scientists. The shift from traditional face-to-face interviews to digital methods became particularly pronounced during the COVID-19 pandemic, necessitating alternative approaches to empirical research [1]. While online interviewing has proven effective in overcoming geographical barriers and logistical constraints [2], certain research settings present additional challenges that reinforce the necessity of digital adaptations. One such setting is the juvenile correctional institution—a closed environment that is not easily accessible to external researchers under normal circumstances. The pandemic further restricted access to these institutions, requiring adjustments in research strategies to ensure the feasibility of data collection while maintaining methodological precision. This study employed a qualitative research framework, using semi-structured interviews with educators working in a juvenile correctional institution to explore their motivations, career trajectories, and perceptions of their roles within the institution, while also examining themes such as job satisfaction, professional development, and societal recognition. Online interviewing facilitated access to this closed research setting, allowing for the remote collection of rich qualitative data. One of the primary benefits of online interviewing was its ability to eliminate geographical constraints, enabling the researcher to engage with participants remotely [2]. Additionally, online interviews provided a cost-effective solution by reducing travel expenses and logistical difficulties associated with in-person data collection [3].
Keywords: online interview; qualitative research; juvenile correctional institution